Gene markers of fracture healing in early stage and the regulatory mechanism during the process using microarray analysis - Chengxue Wang; Baochang Qi; Lei Tan; Jieping Cheng (Acta Orthopaedica et Traumatologica Turcica)
Background: The aim of this study was to explore crucial markers and uncover the regulatory mechanisms of fracture healing in the early stage. Methods: Gene expression profile of GSE45156 was downloaded, in which 3 fractured samples and 3 unfractured samples were used in our present study. Based on the threshold value, differentially expressed genes (DEGs) were selected between two kinds of samples using limma package in R. Enrichment analysis of these DEGs was performed by DAVID software. Furthermore, protein-protein interaction (PPI) network was established integrating information in STRING database, and visualized by Cytoscape software. Results: We identified a set of 960 DEGs including 509 up-regulated and 451 downregulated genes. Biological processes involving RNA splicing and cell cycle were significantly enriched for the up-regulated genes such as Snrpd2, Eftud2, Plk1 and Bub1b, whereas skeletal system development and bone development processes were predominant for down-regulated genes like Ubc. In the constructed PPI network, all the five genes were the predominant nodes, of which Snrpd2 was linked to Eftud2, while Bub1b was to interact with Plk1. Conclusion: Five candidate genes crucial for indicating the process of fracture in early stage were identified. Eftud2, Snrpd2, Bub1b and Plk1 might function through the involvement of cell-cycle-related BP, while Ubc might influence the protein degradation during bone development. However, more experimental validations are needed to confirm these results. Keywords: Fracture healing, Early stage, RNA splicing, Cell cycle, Protein degradation, Protein–protein interaction